A computational exploration of the interactions of the green tea polyphenol (-)-Epigallocatechin 3-Gallate with cardiac muscle troponin C. - Dominic Botten (Public Library of Science (PLoS), 2013)
Thanks to its polyphenols and phytochemicals, green tea is believed to have a number of health benefits, including protecting from heart disease, but its mechanism of action at the molecular level is still not understood. Here we explore, by means of atomistic simulations, how the most abundant of the green tea polyphenols, (-)-Epigallocatechin 3-Gallate (EGCg), interacts with the structural C terminal domain of cardiac muscle troponin C (cCTnC), a calcium binding protein that plays an important role in heart contractions. We find that EGCg favourably binds to the hydrophobic cleft of cCTnC consistently with solution NMR experiments. It also binds to cCTnC in the presence of the anchoring region of troponin I (cTnI(34-71)) at the interface between the E and H helices. This appears to affect the strength of the interaction between cCTnC and cTnI(34-71) and also counter-acts the effects of the Gly159Asp mutation, related to dilated cardiomyopathy. Our simulations support the picture that EGCg interacting with the C terminal domain of troponin C may help in regulating the calcium signalling either through competitive binding with the anchoring domain of cTnI or by affecting the interaction between cCTnC and cTnI(34-71).